The Highways and Side Roads of Statistical Capacity Building - Lokshin, Michael (World Bank, Washington, DC, 2021)
This paper proposes an approach to guide statistical capacity building in developing countries using an analysis based on components of the World Bank’s Statistical Performance Indicator on a sample of 215 countries. The approach demonstrates the importance of expanding traditional capacity-building activities to include programs to strengthen and better monitor user demand for data. Based on this analysis, the paper recommends a two-step strategy for building and enhancing the sustainable statistical capacity of national statistical systems in developing countries. The strategy creates a sustainable trajectory for developing national statistical systems that meet the growing demands of local and global data users. The paper emphasizes the importance of donor coordination and South-South learning initiatives for international capacity-building efforts.